The mesostigmatid mite (Acari: Parasitiformes) fauna of Svalbard: a revised inventory of a high Arctic archipelago - Ávila-Jiménez, María Luisa; Gwiazdowicz, Dariusz J.; Coulson, Stephen James (Zootaxa, 2011)
The need for comprehensive studies of the invertebrate fauna in the high Arctic is increasingly acknowledged in order to more fully understand ecosystem functioning, resilience and to project future changes in the biodiversity and species ranges. Information on the mesostigmatid fauna in the high Arctic is scarce and scattered. Large regions of the high Arctic archipelago of Svalbard, including most of the areas in the east of the island group, have never been surveyed for the mesostigmatid fauna. Furthermore, most of the current knowledge on the mesostigmatid fauna of this important region in the European high Arctic originates from studies in the early 20 th century. Much of the associated slide material no longer exists, either being mislaid or deliberately destroyed, resulting in an ambiguous and potentially misleading mesostigmatid fauna checklist in which identifications and potential synonyms cannot be reliably assessed. Determination of fresh material sampled between 2007–2010 may be an ideal procedure to resolve the great number of uncertainties about the mesostigmatid fauna of the Svalbard archipelago. Twelve out of the 27 species recorded from the Svalbard archipelago were found in the new samples collected from a large number of localities and microhabitats. No new species were identified in the current campaign, and most of the non-observed species are considered to be past missidentifications or potential synonyms. Combining this study with recent publications provides a total mesostigmatid mite diversity for Svalbard of 22 species. This represents the most accurate checklist of the mesostigmatid mite fauna of the archipelago to date.